PENGGUNAAN METODE VAKT UNTUK MENINGKATKAN KEMAMPUAN PENGUASAAN KOSAKTA BAGI MURID TUNARUNGU KELAS VI DI SLB NEGERI 1 GOWA - Uswatun Hasanah; Faizal Faizal; Mustafa Mustafa (-, 2024)
This study examines the low vocabulary mastery ability of deaf students in SLB Negeri 1 gowa. The purpose of this study was to determine: 1) The vocabulary mastery ability of deaf students in Class VI at SLB Negeri 1 Gowa in Baseline 1/A1 condition. 2) The vocabulary mastery ability of Class VI deaf students in SLB Negeri 1 Gowa in the intervention condition through the VAKT method (Intervention/B), 3) The vocabulary mastery ability of Class VI deaf students in SLB Negeri 1 Gowa in the Baseline 2/A2 condition, 4) The vocabulary mastery ability of Class VI deaf students in SLB Negeri 1 Gowa based on the results of the analysis between Baseline 1/A1, intervention (B), and Baseline 2/A2 conditions. Data collection techniques using knowledge tests. The subject of this study was a class VI deaf student with the initials S. The research approach used in this study is a quantitative approach and this type of research uses experimental methods, namely using Single Subject Research (SSR). The results of this study concluded: 1) the ability to master the vocabulary of subject S in the initial condition is very low based on the results of the baseline 1 analysis / (A1), 2) the ability to master the vocabulary of subject S when given the intervention increased to a very high category seen from the analysis in condition (B), 3) the ability to master the vocabulary of subject S after being given treatment increased to a high category seen from the baseline 2 / (A2) condition, 4) the ability to master the vocabulary of subject S based on the results of the analysis between conditions, namely in the initial condition (Baseline1 / A1) the student's ability is very low, increasing to a very high category when given intervention, and from a very high category when given intervention to after given intervention (A2) is in a very high category and the value obtained by subject S is higher than the initial condition (Baseline 1 /A1). Thus the ability to master student vocabulary after being given the intervention is still said to have increased, this is due to an increase in the provision of intervention.